Proving BDI Properties of Agent-Oriented Programming Languages: The asymmetry thesis principles in AgentSpeak(L) - Bordini, Rafael H.; Moreira, Álvaro F. (Annals of mathematics and artificial intelligence, 2004)
In this paper, we consider each of the nine BDI principles defined by Rao and Georgeff based on Bratman's asymmetry thesis, and we verify which ones are satisfied by Rao's AgentSpeak(L), a logic programming language inspired by the BDI architecture for cognitive agents. In order to set the grounds for the proofs, we first introduce a rigorous way in which to define the informational, motivational, and deliberative modalities of BDI logics for AgentSpeak(L) agents, according to its structural operational semantics that we introduced in a recent paper. This computationally grounded semantics for the BDI modalities forms the basis of a framework that can be used to further investigate BDI properties of AgentSpeak(L) agents, and contributes towards establishing firm theoretical grounds for a BDI approach to agent-oriented programming.